World Bank East Asia and Pacific Economic Update - Spring 2022 - World Bank (Washington, DC: World Bank, 2022)
Amidst a fragile recovery, three clouds are gathering over the economic horizon: US inflation could provoke financial tightening, China’s structural slowdown and zero-COVID-19 policy could dampen regional exports, and the conflict between Russia and Ukraine could disrupt food and fuel supplies, spook financial markets, and undermine business confidence. Counterposed against these risks, are three opportunities. First, shifts in the patterns of comparative advantage are creating new niches in both goods and services trade. Second, the diffusion of technologies could boost productivity. Finally, new green technologies could allow countries to cut carbon emissions without unacceptable cuts in consumption or growth. Accordingly, policy action must help countries to both affect the risk and grasp the opportunities. We begin by addressing three proximate questions: What is happening to the economies? Why? And what can we expect? We then discuss the policy options that can help East Asia and Pacific economies weather the shocks and ensure sustainable growth.